2019
DOI: 10.1021/acs.cgd.9b00734
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, Luminescent Properties, and Electrochemical Synthesis of Group 12 Element Coordination Polymers with 4-Substituted 1,2,4-Triazole Ligands

Abstract: The self-assembly of Zn­(II), Cd­(II), or Hg­(II) salts with long flexible 1,2,4-triazole-based ligands resulted in coordination polymers and mononuclear complexes of diverse topology. Indeed, the 1D chain [ZnCl2( btpm )] (1) (P1̅), the 2D square grid [Zn­( btpm )2(H2O)]­(BF4)2·2 btpm ·8H2O (2) (P21212), and the 1D chain [Cd3Cl6( btpm )2]·8H2O (3) (P1̅) with btpm = bis­(4-(1,2,4-triazol-4-yl)­phenyl)­methane were crystallized. In addition, the mononuclear complexes [ZnCl2( ppt )2] (4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…4, each Zn II cation adopts a distorted tetrahedral [ZnN 2 Cl 2 ] coordination environment consisting of two N atoms from two different L ligands [N5 and N6; Zn1-N5 = 2.064 (3) Å and Zn1-N6 = 2.060 (3) Å ] and two coordinated chloride counter-ions [Cl1 and Cl2; Zn1-Cl1 = 2.2161 (11) Å and Zn1-Cl2 = 2.2151 (12) Å ]. The coordination behaviour of the Zn II cation is similar to that reported for other Zn II complexes (Benaissa et al, 2019;Hao et al, 2020;Jones et al, 2012).…”
Section: Figuresupporting
confidence: 82%
“…4, each Zn II cation adopts a distorted tetrahedral [ZnN 2 Cl 2 ] coordination environment consisting of two N atoms from two different L ligands [N5 and N6; Zn1-N5 = 2.064 (3) Å and Zn1-N6 = 2.060 (3) Å ] and two coordinated chloride counter-ions [Cl1 and Cl2; Zn1-Cl1 = 2.2161 (11) Å and Zn1-Cl2 = 2.2151 (12) Å ]. The coordination behaviour of the Zn II cation is similar to that reported for other Zn II complexes (Benaissa et al, 2019;Hao et al, 2020;Jones et al, 2012).…”
Section: Figuresupporting
confidence: 82%
“…Interestingly, Zn-SBF-2 complex displays similar rows with alternating monodentate and bidentate carboxylates along both the directions of the grid, while Zn-SBF-3 complex shows two different rows, one with only bidentate and the other with only monodentate carboxylates along two directions of the grid. Many other sql nets have been given in the literature. …”
Section: Design Strategiesmentioning
confidence: 99%
“…(iv) CPs involving triazole-thiourea based ligands have not been reported, and there are no Hg­(II) complexes with such ligands reported so far, thus increasing interest of the present report. (v) Metal-triazole complexes with Hg­(II) ions have also been rarely reported. , (vi) Recently, we have found that for a given complex, the substituents on the ligand and complex counteranions are important components for modulating the luminescent properties of 1,2,4-triazole complexes . We therefore anticipate that the current triazole-thiourea ligands are potential candidates for the detection of Hg by the formation of luminescent complexes, which is environmentally relevant as mercury and its derivatives are known to be highly toxic pollutants. …”
Section: Introductionmentioning
confidence: 99%